Impact of Pandemic Towards on On-The-Job Training of Criminology Students of Bestlink College of the Philippines Bulacan Campus: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the impact of a pandemic on on-the-job training of criminology students of Bestlink College of the Philippines Bulacan Campus among the 4th-year college students in Bestlink College of the Philippines Bulacan during the school year 2021-2022. The purposive sampling technique is used to get the number of respondents that the researcher needs to use in the questionnaire after getting the total. On January 23, 2020, the novel coronavirus disease COVID-19 was declared a global public health outbreak by the World Health Organization (WHO 2020b). On March 11, 2020, within two months of this initial declaration, COVID-19 was classified by the WHO as the first pandemic to occur from a coronavirus (WHO 2020a), with more than 182,000 confirmed cases in more than 150 different countries and territories around the world (CDC 2020a). According to the Centers for Disease Control and Prevention (CDC), the number of people who COVID-19 could potentially infect will increase until COVID-19 is aggressively controlled (MOH 2020a). Criminology is a science that studies both social and individual criminal behaviour. Psychology, economics, political science, natural science, biology, and human evolution and development are among the disciplines divided. At the same time, other investigators are tasked with determining who committed a crime, and how criminologists are tasked with determining why someone would be motivated to break the law or commit a crime. The field of study has a long and illustrious history and has undergone significant transformations. The researchers used the aim of descriptive design to describe and document the chosen phenomena. This research method explains and identifies the way things are (Fluet 2021). The focus of this research is to describe the chosen phenomenon, which is the satisfaction and confidence of interns from their on-the-job training, especially when the whole nation carries the result of this pandemic that led thousands of educational institutions to down or cease their face-to-face operation. The problem statement gives detailed information about its significance and generates an idea from the respondents' perspective. The study concluded that on the demographic profile of the respondents, which came from criminology students and professor in Bestlink College of the Philippines, the majority of the respondents came from the age of 18-25 years old, single, and in terms of the schedule of OJT interpreted as agree. The factors affecting the student internship were regarded as agree. The groups of respondents’ assessments on the impact of the pandemic on on-the-job training of criminology students of Best Link College of the Philippines Bulacan campus in terms of field training were regarded as 3.76, interpreted as agree. The groups of respondents’ assessment factors affecting the student’s internship were regarded as 3.67, interpreted as agreement. The groups of respondents’ assessments of action taken for criminology students during on-the-job training were regarded as 4.12, interpreted as agree.